(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Evaluation of the effectiveness of Tam ty thang combined with spinal traction in improving radicular syndrome in the treatment of lumbar-hip syndrome due to spinal degeneration. Methods: Clinical intervention research, prospective, comparing before and after treatment. 60 patients in the research used Tam ty thang combined with spinal traction. Results: After 20 days of treatment, the mean VAS pain score decreased from 5.63 ± 1.08 points to 1.27 ± 0.86 points, and the difference compared to before treatment was statistically significant (p < 0.05). The mean Lasègue’s sign angle increased from 55.65 ± 5.18 degrees to 79.30 ± 5.69 degrees; the difference compared to before treatment was statistically significant (p < 0.05). Conclusion: Tam ty thang combined with spinal traction has an analgesic effect and improving radicular syndrome in the treatment of lumbar-hip syndrome due to spinal degeneration.